2021
DOI: 10.3390/insects12111016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Distribution, and Molecular Record of Four Hard Ticks from Livestock in the United Arab Emirates

Abstract: Ticks are important arthropod vectors that serve as reservoirs of pathogens. Rapid urbanization and changes in animal breeding practices could be causing a rise in tick burden on animals. Studies on tick distribution on livestock and tick molecular diversity from the United Arab Emirates (UAE) are limited. The aim of this study was to (i) provide molecular and morphological identification of tick species, (ii) compare tick infestation between different hosts, (iii) compare tick infestation in relation to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…In the present study, a seasonal variations of camels infestation were higher in summer (93.7%), and the lowest infestation occur in winter (44.4%), This agreed with Nourollahi Fard et al (2012), Moshaverinia and Moghaddas (2015), Hassan et al (2017), Perveen et al (2020) andShamsi et al (2020). But, this disagreed with Bala et al (2018) they found that the autumn rate was (40.22%), followed by winter (30.07%) and summer (29.71%).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, a seasonal variations of camels infestation were higher in summer (93.7%), and the lowest infestation occur in winter (44.4%), This agreed with Nourollahi Fard et al (2012), Moshaverinia and Moghaddas (2015), Hassan et al (2017), Perveen et al (2020) andShamsi et al (2020). But, this disagreed with Bala et al (2018) they found that the autumn rate was (40.22%), followed by winter (30.07%) and summer (29.71%).…”
Section: Resultssupporting
confidence: 92%
“…In the present study, the face, udder, testes, hind limbs, and tail were the most infested site with rate of (97.5%, 1160/1190) for each, followed by fore limbs (96.6%, 1150/ 1190), chest (94%, 1120/1190), and abdomen (92.4%, 1100/ 1190). This more or less agreed with Nazifi et al (2011) in Iran found adult ticks on axilla (36%), groin (20%), interdigital cleft (14%), genital area (12%), anus (10%), tail-brush (4%) and ears (4%), Nourollahi Fard et al (2012) found that perineum and chest infested rate was (91.1%), external ear (6.3%), shoulder (2.6%), Perveen et al (2020) reported that most c ticks were found attached to the perianal, and vulvar regions, the inner surface of thighs, udder, and inguinal region, but fewer ticks were on pinna, and tchest region, Al-Deeb and Muzaffar (2020) found that the highest number of ticks were on tail area followed by abdomen, and Elati et al (2021) in Tunisia illustrated the preferred attachment sites for adult Hyalomma ticks were the sternum (38.3%), around the anus (36.2%), udder (18.4%), and inner thigh (6.9%).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, ticks were identified at the molecular level using 16S rRNA gene with the primers 16S+1 and 16S−1 (5′-CTGCTCAATGATTTTTTAAATTGCTGTGG-3′ and 5′-CCGGTCTGAACTCAGATCAAGT-3′, respectively). The details of sample processing, DNA extraction, and PCR conditions had been mentioned elsewhere ( 36 ). The mean monthly temperature in degrees Celsius (°C) was obtained from the nearest meteorological station.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, CCHFV antibodies were detected in dromedary camels in two different studies (10,68) (Table 1). Hyalomma ticks are the most prevalent vector species reported on camels, cows, sheep, and goats in the UAE (106)(107)(108). Therefore, continued surveillance, monitoring, and screening of tick vectors, animals, and associated people are required to prevent any future CCHF outbreak.…”
Section: United Arab Emiratesmentioning
confidence: 99%